Endogenous event-related potentials in patients with primary Sjögren's syndrome without central nervous system involvement. (2nd November 2015) - Dziadkowiak, E; Sebastian, A; Wiland, P; Waliszewska-Prosół, M; Wieczorek, M; Zagrajek, M; Ejma, M
Abstract : Objectives: Endogenous cognitive event-related potentials (CERPs) reflect higher-level processing of sensory information and can be used to evaluate cognitive functions. The aim of this paper was to determine whether there are any abnormalities in the electrophysiological parameters of CERPs in patients with primary Sjögren's syndrome (pSS) but without symptoms of central nervous system (CNS) involvement or mental disorder. The analysis of CERP parameters was then correlated with the clinical status of the patients and with some of the immunological parameters in the patient group. Method: Thirty consecutive patients with pSS (29 females, one male) were included in the study. All the patients underwent CERP examination. Results: There was a significant prolongation of the latency of P300 and N200 potentials in patients with pSS. Abnormalities in electrophysiological parameters of CERPs correlated with the duration of the disease, salivary gland abnormalities, and elevated erythrocyte sedimentation rate (ESR) values. Patients with coexisting chronic fatigue syndrome (CFS) had larger P300 amplitudes. There were no statistically significant changes in the electrophysiological parameters of CERPs in patients with pSS dependent on the presence of peripheral nervous system (PNS) lesions, skin changes, arthritis, abnormalities in white blood cells and the immune system or the levels of blood lipids. Conclusions: The results of the study suggest the presence of a minor cognitive dysfunction in patients with pSS without symptoms of CNS involvement or mental disorder. Cognitive dysfunction correlated with the disease duration time and the severity of inflammatory changes (salivary gland abnormalities and inflammatory markers in the blood). Further and larger longitudinal studies are necessary for confirmation of this correlation.